1993
DOI: 10.1002/1097-0142(19930315)71:6<2055::aid-cncr2820710621>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Cystosarcoma phyllodes of the seminal vesicle

Abstract: An unique case of high‐grade phyllodes tumor (cystosarcoma phyllodes) arising in the seminal vesicle is reported. A 61‐year‐old man had symptoms of urinary obstruction, and ultrasonography and computed tomography showed a large mass posterior to the bladder. Using cystoprostatoseminovesiculectomy, a high‐grade phyllodes tumor of the left seminal vesicle was found that did not involve the bladder or prostate. Histologically, the tumor consisted of benign irregular slit‐like glands set in a mitotically active ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 13 publications
0
22
0
4
Order By: Relevance
“…Fain JS et al reported the first case of high-grade phyllodes tumor of the seminal vesicle, with a lung metastasis four years after cystoprostatoseminovesiculectomy. They proposed that like breast and prostate tumors, phyllodes tumors of the seminal vesicle should be considered high-grade lesions (malignant) with significant mitotic activity, stromal pleomorphism, and stromal overgrowth [8]. Abe et al reported a patient suffering from cystosarcoma phyllodes of the seminal vesicle who died 11 months after tumor removal by open operation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Fain JS et al reported the first case of high-grade phyllodes tumor of the seminal vesicle, with a lung metastasis four years after cystoprostatoseminovesiculectomy. They proposed that like breast and prostate tumors, phyllodes tumors of the seminal vesicle should be considered high-grade lesions (malignant) with significant mitotic activity, stromal pleomorphism, and stromal overgrowth [8]. Abe et al reported a patient suffering from cystosarcoma phyllodes of the seminal vesicle who died 11 months after tumor removal by open operation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Phyllodes tumors with varying degrees of malignant potential have been reported in the prostate, including cystosarcoma phyllodes. Adenofibroma and adenosarcoma of the female genital tract are histologically similar to phyllodes tumors and are considered of müllerian origin [4]. …”
Section: Discussionmentioning
confidence: 99%
“…17,[51][52][53][54][55][56][57][58][59][60][61] There are at least two reported cases of stromal sarcoma of the 'phyllodes type' arising in the seminal vesicle without involvement of the prostate. 62 suggesting a potential for STUMPs to dedifferentiate into sarcomas in rare cases and justifying the term 'malignant potential' for STUMPs. 3 Indeed, in Herawi and Epstein's series of 50 stromal tumours of the prostate, seven of 14 stromal sarcomas were associated with STUMP.…”
Section: Rhabdomyosarcomamentioning
confidence: 99%